IMPLEMENTATION OF THE REVITALISATION OF THE SUKALILA RIVERBANK AS A GREEN OPEN SPACE IN THE CITY OF CIREBON - Muhammad Rizki Meidianto (Law Research Review Quarterly, 2026)
The revitalisation of riverbanks is one of the government’s initiatives to redevelop urban areas whilst restoring the ecological functions of rivers that have long suffered degradation due to uses that contravene spatial planning regulations. The Sukalila riverbank in Cirebon City is one such area facing these issues, where settlements have been built on the riverbank, thereby disrupting environmental functions and causing various problems, such as flooding, pollution, and a decline in environmental quality. These conditions have prompted the local government to carry out enforcement and revitalisation of the riverbank area, transforming it into a betterorganised and sustainable green open space (RTH). This study aims to analyse the implementation of the Sukalila Riverbank revitalisation policy and to identify the factors hindering its implementation. The research method employed is a legal-empirical approach with a qualitative descriptive methodology, examining applicable legal provisions and factual conditions on the ground. Data were obtained through literature review and analysis of regulations pertaining to spatial planning, the environment, and water resource management. The research findings indicate that the implementation of the revitalisation of the Sukalila River banks has  progressed through the stages of building regulation, area planning, and the development of green open spaces. However, its implementation has not yet been fully optimal as it continues to face various obstacles, such as community resistance, resource constraints, and a lack of coordination between agencies. Furthermore, the gap between legal norms and on-theground realities also poses a challenge in achieving area planning that complies with applicable regulations. Consequently, more comprehensive and sustainable efforts are required—from legal, social, and institutional perspectives—to ensure that the implementation of riverbank revitalisation policies proceeds effectively and delivers optimal benefits for both the community and the environment.